Inorganic curing agent with good curing effect and preparation method thereof

Through the synergistic effect of nano-silica sol and nano-alumina sol and combined with epoxy-based modified nano-silica sol, the problems of insufficient application and poor curing effect of phosphogypsum in road engineering are solved, and high strength and compactness are achieved And the curing effect of not prone to cracks meets the needs of road construction and low-temperature environment.

CN116120031BActive Publication Date: 2025-01-07HUBEI JIUXIA ENTERPRISE MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211628248.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-17
Publication Date
2025-01-07
Estimated Expiration
2042-12-17

AI Technical Summary

Technical Problem

The application of existing solid waste phosphogypsum in road engineering construction is limited by its insufficient mechanical properties and poor water stability, and the existing curing agent has problems such as poor curing effect or cracks occur after a long period of time.

Method used

Using nano-silica sol and phosphogypsum, cement and other raw materials, the content and pH value of nano-silica sol are controlled to promote early hydration of cement and material structural stability, combining epoxy-modified nano-silica sol and nano-silica sol The coordinated combination of alumina sols forms a high-strength, dense and not prone to cracks.

Benefits of technology

It realizes efficient curing of phosphogypsum, improves the mechanical properties and waterproof and permeability of the material, avoids cracks after curing, and meets the requirements of road construction and harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004004533670000071
    Figure BDA0004004533670000071
Patent Text Reader

Abstract

The invention discloses an inorganic curing agent with good curing effect and a preparation method thereof, and relates to the field of curing agents. The inorganic curing agent comprises the following raw materials by weight: 20-30 parts of silicon-based materials, 0.1-5 parts of metal oxides, 0.1-0.5 parts of functional additives, and 60-72 parts of water. The inorganic curing agent prepared by the invention is compounded with raw materials such as cement and gypsum to achieve a good curing effect, and will not produce cracks after long-term use, and the solidification and strength of the curing are high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of curing agents, and in particular to an inorganic curing agent with good curing effect and a preparation method thereof. Background Art

[0002] Due to the diversity of land types in my country, this poses a great challenge to the foundations in rainy areas. The erosion of rainwater has a great negative impact on the foundation and affects its service life. Curing agent is a new type of environmentally friendly and energy-saving material, which is synthesized from one or more organic and inorganic materials. It can solidify various types of soil, thereby increasing the various properties of the solidified soil and improving the service life and compressive strength of the soil. General curing agents can be divided into four categories: inorganic curing agents, organic curing agents, bio-enzyme curing agents and ionic curing agents.

[0003] The effective utilization rate of existing solid waste phosphogypsum is low, mainly because the mechanical properties of phosphogypsum are insufficient and the water stability is poor, which greatly limits its application in the field of road engineering construction. In order to fully utilize the bulk solid waste phosphogypsum, an inorganic curing agent is prepared with silicon dioxide as the main raw material, and the mechanical properties of phosphogypsum are improved by effectively curing phosphogypsum, thereby overcoming the shortcomings of phosphogypsum in road engineering construction. Patent CN111138099A discloses a curing agent for phosphogypsum waste residue and a curing method thereof, which reduces environmental pollution by adding an activator component and reacting the components with each other, but cracks are generated after long-term curing. Patent CN108585576B discloses a phosphogypsum curing agent, which reduces and encapsulates harmful components in the material by adding a reducing agent and a gelling agent, thereby achieving the reuse of phosphogypsum, but there is a problem of poor curing effect. In order to overcome the above problems, the present invention provides an inorganic curing agent with good curing effect and a preparation method thereof, which has a good curing effect, does not produce cracks after long-term use, and has high solidification density and strength. Summary of the invention

[0004] The present invention provides an inorganic curing agent with good curing effect and a preparation method thereof, which can be combined with raw materials such as cement and phosphogypsum to achieve a good curing effect. No cracks will be generated after long-term use, and the solidification density and strength are high.

[0005] The present application provides an inorganic curing agent with good curing effect, which comprises the following preparation raw materials by weight: 20-30 parts of silicon-based materials, 0.1-5 parts of metal oxides, 0.1-0.5 parts of functional additives, and 60-72 parts of water.

[0006] In a preferred embodiment, the silicon-based material is an inorganic silicon-based material and / or an organic silicon-based material. Preferably, the inorganic silicon-based material is at least one of silicon dioxide, sodium silicate, potassium silicate, and lithium silicate. Preferably, the organic silicon-based material is at least one of sodium methyl silicate and potassium methyl silicate. Further preferably, the silicon-based material is silicon dioxide.

[0007] In a preferred embodiment, the silicon dioxide is selected from one or a combination of fumed silicon dioxide, silicon dioxide aerogel, nano silicon dioxide powder, and nano silicon dioxide sol.

[0008] Preferably, the silicon dioxide is nano-silica sol, the content of silicon dioxide in the nano-silica sol is 14-31wt%, and the pH of the nano-silica sol is 5-11.

[0009] Further preferably, the content of silicon dioxide in the nano-silica sol is 25-31 wt %, and the pH of the nano-silica sol is 7-11.

[0010] The effective utilization rate of existing solid waste phosphogypsum is low. The main reason is that the mechanical properties of phosphogypsum are insufficient and the water stability is poor, which greatly limits its application in the field of road engineering construction. In order to fully utilize the bulk solid waste phosphogypsum, an inorganic curing agent is prepared with silicon dioxide as the main raw material. The mechanical properties of phosphogypsum are improved by effective curing of phosphogypsum, and the shortcomings of phosphogypsum in road engineering construction are overcome. During the exploration process, the inventors found that different silicon dioxides have great differences in the curing effects of phosphogypsum. When the silicon dioxide in the system is nano-silica sol, it is in full contact with the phosphogypsum powder. During the compaction process, the free water in the phosphogypsum is gradually discharged, the pores between the particles are reduced, the volume is reduced, and the connection between the particles is enhanced, so that the phosphogypsum powder is permanently cured, the solidification density and strength are high, and no cracks will occur after long-term use. After the silica aerogel is solidified with raw materials such as cement and phosphogypsum, many uneven pores are formed inside the later solidified material, which greatly reduces the material's waterproof and anti-seepage properties and mechanical properties. This may be because the silica aerogel absorbs more gas, which releases bubbles during the mixing process with raw materials such as phosphogypsum and cement, resulting in an increase in the porosity inside the solidified material.

[0011] The inventor unexpectedly discovered that the content of silica in the nano-silica sol affects the effect of cement hydration and the mechanical properties of the cured material. By controlling the content of silica in the nano-silica sol in the system to 14-31wt%, especially the nano-silica sol with a content of 25-31wt%, the early hydration of cement is promoted, the transition zone between cement paste and phosphogypsum is improved, and the internal structural stability of the cured material is improved. The inventor speculates that the reason may be that the volcanic ash activity of the nano-silica sol with a content of 25-31wt% is high, and it can react with calcium hydroxide in the cement paste to form a gel, provide active sites for cement hydration, promote cement hydration, fill in the gaps between particles, modify the microstructure inside the material, reduce porosity, and improve mechanical properties. Based on the system of the present invention, by controlling the pH of the nano-silica sol to 5-11, especially controlling the pH of the nano-silica sol to 7-11, it is compatible with the alkaline environment of phosphogypsum and cement, and is not easy to agglomerate. When the content of silicon dioxide in the nano-silica sol is higher than 31wt% and the pH is lower than 5, the nano-silica inevitably agglomerates, which affects the reactivity of the nano-silica with calcium hydroxide, affects the hydration and curing effect of cement, forms weak areas in the material, and leads to a decrease in the mechanical properties of the cured material. Further preferably, the content of silicon dioxide in the nano-silica sol is 28wt% and the pH is 9.

[0012] In a preferred embodiment, the nano-silica sol is at least one of epoxy-modified nano-silica sol, alkyl-modified nano-silica sol, and organosilicon-modified nano-silica sol.

[0013] Preferably, the nano-silica sol is epoxy-modified nano-silica sol, and the model of the epoxy-modified nano-silica sol is SC-102, which is sourced from Jinan Yinfeng Silicon Products Co., Ltd.

[0014] Based on the system of the present invention, nano-silica sol is used, and the curing effect with raw materials such as phosphogypsum and cement is good. The cured material has good mechanical properties, but the fluidity of the slurry after mixing with raw materials such as phosphogypsum and cement is reduced. This may be because the nano-silica sol has a high specific surface area and surface energy, adsorbs free water in the slurry, and reduces the fluidity of the slurry. During the exploration process, the inventor found that by introducing epoxy groups to modify the nano-silica sol, good dispersion in raw materials such as phosphogypsum and cement can be achieved, and the fluidity of the slurry can be effectively improved. The inventor speculates that the reason may be that the introduction of epoxy groups in the nano-silica sol structure can improve the hydrophobicity of the nano-silica sol, reduce the combination of the nano-silica sol and the free water in the slurry, and improve the fluidity of the slurry. In addition, the inventor unexpectedly discovered that the introduction of epoxy-modified nano-silica sol forms smaller aggregates when mixed with phosphogypsum and cement. The smaller aggregates are used as fillers to fill the gaps between phosphogypsum and cement particles, which play a bonding role on the powder particles, reduce porosity, and improve the splitting strength, flexural tensile strength and unconfined compressive strength of the cured material. However, the aggregates formed by organosilicon-modified nano-silica sol when mixed with phosphogypsum and cement are larger. The larger aggregates tend to push away the surrounding powder particles, resulting in an increase in the void space. At the same time, the larger aggregates absorb a large amount of free water, which seriously reduces the fluidity of the slurry and the mechanical properties of the cured material.

[0015] In a preferred embodiment, the metal oxide is selected from at least one of titanium oxide, aluminum oxide, zinc oxide and zirconium oxide.

[0016] Preferably, the metal oxide is aluminum oxide; preferably, the aluminum oxide is nano aluminum oxide sol, and the particle size of the nano aluminum oxide sol is 10-20 nm.

[0017] As a preferred technical solution, the pH of the nano alumina sol is 3-9; preferably, the pH of the nano alumina sol is 7-9;

[0018] The model of the nano alumina sol is CYL10B, which was purchased from Hangzhou Jiupeng New Materials Co., Ltd.

[0019] Based on the system of the present invention, by introducing metal oxide alumina, especially introducing nano alumina sol with a pH of 7-9 and a particle size of 10-20nm, a uniformly dispersed and stable nano silica-nano alumina composite sol is formed with the nano silica sol in the system, so that the provided inorganic curing agent can achieve a good curing effect after being mixed with raw materials such as phosphogypsum and cement, thereby further improving the strength of the cured material. The inventor speculates that the reason may be that the nano-alumina sol with a pH of 7-9 and a particle size of 10-20nm has a high compatibility with the nano-silica sol in the system, and has good dispersibility during mixing, weakening the random aggregation tendency between the nano-silica sols, forming a uniformly dispersed and stable nano-silica-nano-alumina composite sol, and when mixed with raw materials such as phosphogypsum and cement, a colloidal chemical reaction occurs with the powder raw materials to achieve a good curing effect, and an aluminum-oxygen-bound octahedral network structure and a silicon-oxygen-bound tetrahedral network structure are constructed, further improving the strength of the cured material, and when the pH of the nano-alumina sol introduced into the system is lower than 7, charge neutralization occurs with the nano-alumina sol to form a larger nano-particle aggregate, and during subsequent curing, it is impossible to exchange charges with phosphogypsum and cement, which seriously affects the curing effect and the comprehensive performance of the cured material. Preferably, the pH of the nano-alumina sol is 9.

[0020] As a preferred technical solution, the mass ratio of the silicon-based material and the metal oxide is (20-30):(0.5-1.2); preferably, the mass ratio of the epoxy-modified nano-silica sol and the nano-alumina sol is (20-30):(0.5-1.2).

[0021] Based on the system of the present invention, by controlling the mass ratio of the epoxy-modified nano-silica sol and the nano-alumina sol in the system to (20-30): (0.5-1.2), the epoxy-modified nano-silica sol and the nano-alumina sol can maximize the synergistic compounding effect, so that after the provided curing agent is cured with raw materials such as cement and gypsum, a solid material with a silicon-oxygen-combined tetrahedral network structure as the main component and an aluminum-oxygen-combined octahedral network structure as the auxiliary component is obtained, while ensuring the splitting strength, flexural tensile strength and unconfined compressive strength of the solid material, while avoiding the increase of low-temperature brittleness of the cured material due to the excessive content of the nano-alumina sol, so that the provided inorganic curing agent is widely used in road construction in different regions and meets the use requirements under cold climate conditions in northern regions.

[0022] In a preferred embodiment, the functional additive is at least one of 4,5-dichloro-2-octyl-3-isothiazolinone, 1,2-benzisothiazol-3-one, and 2-(1,3-thiazol-4-yl)benzimidazole.

[0023] Preferably, the functional additive is 4,5-dichloro-2-n-octyl-3-isothiazolinone, which is purchased from Beijing Bailingwei Technology Co., Ltd.

[0024] Based on the invention of this system, the addition of 4,5-dichloro-2-octyl-3-isothiazolinone is not easy to react with other substances in this system, has good stability, can effectively improve the anti-mildew and antibacterial effect and anti-mildew time of the inorganic curing agent, and improve the wide applicability of the inorganic curing agent in harsh environments.

[0025] Another aspect of the present invention provides a method for preparing an inorganic curing agent with good curing effect, which comprises mixing silicon dioxide, metal oxide, functional additive and water by weight and stirring the mixture evenly at room temperature to obtain the inorganic curing agent.

[0026] The present invention produces the following beneficial effects: 1) by using a specific nano-silica sol as a preparation raw material, after solidification with raw materials such as cement and gypsum, no cracks will be generated after long-term use, and the solidified density and strength are high; 2) by modifying the nano-silica sol, the slurry fluidity is effectively improved, and the comprehensive performance of the solidified material is guaranteed; 3) the nano-silica sol and the nano-alumina sol act synergistically to further improve the curing effect and the strength of the solidified material; 4) the synergistic compounding effect of the epoxy-modified nano-silica sol and the nano-alumina sol avoids the increase of brittleness of the material due to excessive hardness after solidification, and meets the use requirements of low-temperature environments. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below with reference to specific embodiments.

[0028] Example 1

[0029] Embodiment 1 of the present invention specifically provides an inorganic curing agent with good curing effect, which comprises the following preparation raw materials in parts by weight: 25 parts of silicon-based material, 0.8 parts of metal oxide, 0.3 parts of functional additive, and 66 parts of water.

[0030] The silicon-based material is silicon dioxide, which is epoxy-modified nano-silica sol, the silicon dioxide content of the epoxy-modified nano-silica sol is 28wt%, the pH is 9, the model of the epoxy-modified nano-silica sol is SC-102, and it comes from Jinan Yinfeng Silicon Products Co., Ltd.

[0031] The metal oxide is nano alumina sol with a particle size of 10-20 nm and a pH of 9. The model of the nano alumina sol is CYL10B, which is purchased from Hangzhou Jiupeng New Materials Co., Ltd.

[0032] The functional additive 4,5-dichloro-2-n-octyl-3-isothiazolinone was purchased from Beijing Bailingwei Technology Co., Ltd.

[0033] The inorganic curing agent is obtained according to the following preparation process: silicon-based material, metal oxide, functional additive and water are mixed by weight, and then stirred evenly at room temperature to obtain the inorganic curing agent.

[0034] Example 2

[0035] Embodiment 2 of the present invention specifically provides an inorganic curing agent with good curing effect, which comprises the following preparation raw materials in parts by weight: 20 parts of silicon-based material, 0.5 parts of metal oxide, 0.1 parts of functional additive, and 60 parts of water.

[0036] The silicon-based material is silicon dioxide, which is epoxy-modified nano-silica sol, the silicon dioxide content of the epoxy-modified nano-silica sol is 25wt%, the pH is 7, the model of the epoxy-modified nano-silica sol is SC-102, and it comes from Jinan Yinfeng Silicon Products Co., Ltd.

[0037] The metal oxide is nano alumina sol with a particle size of 10-20 nm and a pH of 7. The model of the nano alumina sol is CYL10B, which is purchased from Hangzhou Jiupeng New Materials Co., Ltd.

[0038] The functional auxiliary agent is the same as that in Example 1, and the preparation method is the same as that in Example 1.

[0039] Example 3

[0040] Embodiment 3 of the present invention specifically provides an inorganic curing agent with good curing effect, which comprises the following preparation raw materials in parts by weight: 30 parts of silicon-based material, 1.2 parts of metal oxide, 0.5 parts of functional additive, and 72 parts of water.

[0041] The silicon-based material is silicon dioxide, which is epoxy-modified nano-silica sol, the silicon dioxide content of the epoxy-modified nano-silica sol is 31wt%, the pH is 11, the model of the epoxy-modified nano-silica sol is SC-102, and it comes from Jinan Yinfeng Silicon Products Co., Ltd.

[0042] The metal oxide is nano alumina sol with a particle size of 10-20 nm and a pH of 9. The model of the nano alumina sol is CYL10B, which is purchased from Hangzhou Jiupeng New Materials Co., Ltd.

[0043] The functional auxiliary agent is the same as that in Example 1, and the preparation method is the same as that in Example 1.

[0044] Comparative Example 1

[0045] Comparative Example 1 of the present invention specifically provides an inorganic curing agent with good curing effect. Its specific implementation method is the same as that of Example 1, except that the silicon dioxide is an alkyl-modified nano-silica sol, and the model of the alkyl-modified nano-silica sol is SC-201, which is purchased from Jinan Yinfeng Silicon Products Co., Ltd.

[0046] Comparative Example 2

[0047] Comparative Example 2 of the present invention specifically provides an inorganic curing agent with good curing effect. Its specific implementation is the same as that of Example 1, except that the mass ratio of the epoxy-modified nano-silica sol to the nano-alumina sol is 20:0.05.

[0048] Comparative Example 3

[0049] Comparative Example 3 of the present invention specifically provides an inorganic curing agent with good curing effect. Its specific implementation method is the same as that of Example 1, except that the metal oxide is aluminum oxide, model SL22, purchased from Zhengzhou Dafeng Micropowder Co., Ltd.

[0050] Comparative Example 4

[0051] Comparative Example 4 of the present invention specifically provides an inorganic curing agent with good curing effect. Its specific implementation method is the same as that of Example 1, except that the silica is nano silica sol, model CY-S01A, purchased from Hangzhou Jiupeng New Materials Co., Ltd.

[0052] Performance Testing

[0053] According to the standard JTG E51-2009, the curing agent samples prepared in the embodiments and comparative examples were mixed with cement and gypsum (the amount of curing agent added was 6% of the total mass of cement and phosphogypsum), and then construction was carried out and the mechanical properties were tested. The mechanical properties test included: splitting strength (28d), unconfined compressive strength (7d), and flexural tensile strength; according to the standard GB / T50082-2009, the water permeability test was carried out, the penetration pressure was maintained at 1.0MPa, and the water seepage depth was tested after 8h.

[0054] The test results are shown in Table 1

[0055] Table 1

[0056]

Claims

1. An inorganic curing agent with good curing effect, characterized in that: The preparation raw materials include the following by weight: 20-30 parts of silicon-based materials, 0.1-5 parts of metal oxides, 0.1-0.5 parts of functional additives, and 60-72 parts of water; The silicon-based material is silicon dioxide, the silicon dioxide is nano-silica sol, the content of silicon dioxide in the nano-silica sol is 14-31wt%, the pH of the nano-silica sol is 5-11, and the nano-silica sol is epoxy-modified nano-silica sol; The metal oxide is aluminum oxide; the aluminum oxide is nano aluminum oxide sol, the particle size of the nano aluminum oxide sol is 10-20 nm; the pH of the nano aluminum oxide sol is 7-9; The mass ratio of the silicon-based material to the metal oxide is (20-30): (0.5-1.2).

2. An inorganic curing agent with good curing effect as claimed in claim 1, characterized in that: The functional auxiliary agent is at least one of 4,5-dichloro-2-n-octyl-3-isothiazolinone, 1,2-benzisothiazol-3-one and 2-(1,3-thiazol-4-yl)benzimidazole.

3. A method for preparing an inorganic curing agent with good curing effect as claimed in any one of claims 1 to 2, characterized in that: The method comprises the following steps: mixing silicon-based materials, metal oxides, functional additives and water according to weight, and stirring the mixture evenly at room temperature to obtain the product.

Citation Information

Patent Citations

  • A phosphogypsum curing agent

    CN108585576B

  • Curing agent and curing method for phosphogypsum waste residues

    CN111138099A

  • Preparation method of tailings hydraulic road base material

    CN108516766A